2010
DOI: 10.1179/136217110x12665048207610
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intermetallic layer in dissimilar TIG welding–brazing butt joint of aluminium alloy to stainless steel

Abstract: Intermetallic layer of dissimilar tungsten inert gas welding-brazing butt joint of aluminium alloy/ stainless steel has been studied. A visible unequal thickness intermetallic layer has formed in welded seam/steel interface, and the thickness of the whole layer is ,10 mm. The interface with Al-12Si filler metal consists of t 5 -Al 8 Fe 2 Si layer in welded seam side and h-(Al,Si) 13 Fe 4 layer in steel side with the hardness values of 1025 and 835 HV respectively, while the interface with Al6Cu filler metal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…Whether this high boron steel can be welded, it need to test and systematically research. Gas tungsten arc welding (TIG) is a widely used welding method for its high quality welds and relatively lower equipment investment [12][13][14][15] . In this process, a tungsten electrode is shielded by a flow of inert and/or reducing gases such as argon (normally employed), helium, nitrogen, hydrogen or blends.…”
mentioning
confidence: 99%
“…Whether this high boron steel can be welded, it need to test and systematically research. Gas tungsten arc welding (TIG) is a widely used welding method for its high quality welds and relatively lower equipment investment [12][13][14][15] . In this process, a tungsten electrode is shielded by a flow of inert and/or reducing gases such as argon (normally employed), helium, nitrogen, hydrogen or blends.…”
mentioning
confidence: 99%
“…Secondly, Al could easily interact with Fe to produce Fe-Al phase ensuring the metallurgical bonding at the interface. Thirdly, Al had a relatively large solid solubility in Mg, indicating it could be added through filler similar to Al-based filler in previous studies [28,29]. It has been reported that the interfacial reaction of Al/Fe was suppressed by adding alloying elements such as Si and Cu into the Al-based filler.…”
Section: The Role Of Micro-alloying Element Almentioning
confidence: 69%
“…Fig. 4 shows the schematic diagram of the four Nguyen et al 40) Shah et al 41) Zhang et al 63) Wang et al 70) Liu et al 71) Tungsten inert gas (TIG) welding Borrisutthekul et al 42) Song et al 43) Liu et al 64) Wang et al 72) Resistance spot welding (RSW) Pouranvari et al 44) Qui et al 45) Satonaka et al 46) Winnicki et al 47) Baskoro et al 48) Su et al 49) Ibrahim et al 50) Oikawa et al 51) Sun et al 52) Zhang et al 65) Sun et al 66) Min et al 73) Feng et al 74) Laser welding Torkamany et al 53) Dharmendra et al 54) Chang et al 67) Liu et al 64) Li et al 75) Cold metal transfer (CMT) Jácome et al 55) Kang et al 56) Shang et al 68) Ren et al 76) Friction stir welding (FSW) Watanabe et al 57) Morishige et al 69) Chang et al 67) Czerwinski et al 77) Element welding Meschut et al 58) Qui et al 59) Ling et al 60) Ling et al 61) Meschut et al 58) Absar et al 62) Manladan et al 78) Manladan et al 79)…”
Section: Steel-aluminum Weldingunclassified